Damage Detection of Retrofitted Beam using Frequency Response Function - Kumar, Yogesh (My University, 2011)
Structures are assembles of loaded carrying members capable of safely transferring the superimposed loads to the foundations. They are constructed (e.g. buildings, bridges, dams, transmission towers, etc.) or manufactured (e.g. machines, trains, ships, aircraft, etc.) to serve specific functions during their design lives. In order to serve their designated functions, the structures must satisfy both strength and serviceability criteria throughout their stipulated design life. However, with the passage of time, some amount of deterioration and damages are bound to occur, due to variety of factors; such as environment degradation, fatigue, excessive loads etc. Knowledge of these defects with a view to detect and evaluate them and then minimizing them in the structures are essential to achieve improved and acceptable level of quality. An improvement in the structures quality increases its reliability and in turns the safety of the machines and equipment. There is, therefore, a need to have methods by which the defects in the structures can be examined without affecting their performance. Non- Destructive Testing (NDT), Non-Destructive Evaluation (NDE) and Non-Destructive Inspection (NDI) are the terms used in this connection to represent the techniques that are based on the application of physical properties employed for the purpose of detecting and assessing the irregularities and harmful defects without impairing the usefulness of such structures. Many old building needs to be retrofitted because they have not been designed by taking in to considerations earthquake forces. SHM of such buildings is also very important in order to study the vibration characteristics. Seismic retrofitting of existing structures is one of the effective methods for improving the performance of the structure in future loading. Various terms are associated to retrofit with a marginal difference like repair, strengthening, retrofitting, remoulding, rehabilitation, reconstruction etc. But there is no consensus on them. Various retrofitting techniques are used in field and out of all plate bonding techniques are considered as the best. In the plate bonding technique the plates of different material viz Carbon Fibre Reinforced Polymer (CFRP), Glass Fibre Reinforced Polymer (GFRP), Ferro cement etc. are bonded to the surface of structural member to increase its strength. In the present work GFRP material is used for Plate bonding. The present research deals with Damage detection of Retrofitted beams by Frequency response function. In this research we modelled RCC beam as control beam in ANSYS. The size of the beam is 117X227X4100 mm. Damage was introduced in the beam by doing the deformation controlled non-linear analysis. Retrofitted beam is modelled in ANSYS and damage of the beam is introduced using the same procedure. To model a damaged beam we used the Elastic modulus calculated using the Load deflection value observed through the non linear analysis of the beams. Retrofitted beams are modelled as stressed at 90% and 75%. Harmonic analysis is done on the control beam and retrofitted beam at different load steps. By doing the harmonic analysis we get the frequency response function at that load step. Using the frequency response function we analysed the damage. From the research we conclude that there is increase in frequency of retrofitted beam in comparison to control beam; also the load carrying capacity of beam increases after retrofitting. We also observed increase stiffness of beam after retrofitting. In the second phase of this research is to compare the results with the experimental results and try to identify the various effects on the RCC structural members. The result show good agreement with the experimental results.
M.E. (CED)
Keywords: Frequency response function; structures; non destructive testing; NDT; non destructive evaluation; non destructive inspection